2022
DOI: 10.3390/cancers14051132
|View full text |Cite
|
Sign up to set email alerts
|

Toward More Comprehensive Homologous Recombination Deficiency Assays in Ovarian Cancer, Part 1: Technical Considerations

Abstract: High-grade serous ovarian cancer (HGSOC), the most frequent and lethal form of ovarian cancer, exhibits homologous recombination deficiency (HRD) in 50% of cases. In addition to mutations in BRCA1 and BRCA2, which are the best known thus far, defects can also be caused by diverse alterations to homologous recombination-related genes or epigenetic patterns. HRD leads to genomic instability (genomic scars) and is associated with PARP inhibitor (PARPi) sensitivity. HRD is currently assessed through BRCA1/2 analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 181 publications
(227 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, assessing the predictive value of initial biomarkers allowed us to decipher more robust ones (i.e., less sensitive to evolutionary fluctuations); furthermore, iterative biopsies with multiple molecular assays are not necessarily compatible with real-life practice. Thirdly, it is now well-known that HRD status may be assessed through diverse companion diagnostic assays; they nevertheless do not overlap perfectly [ 7 ]. The MyChoice ® assay has been shown to represent the current gold standard in ovarian cancer as a prerequisite to PARPi challenge [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, assessing the predictive value of initial biomarkers allowed us to decipher more robust ones (i.e., less sensitive to evolutionary fluctuations); furthermore, iterative biopsies with multiple molecular assays are not necessarily compatible with real-life practice. Thirdly, it is now well-known that HRD status may be assessed through diverse companion diagnostic assays; they nevertheless do not overlap perfectly [ 7 ]. The MyChoice ® assay has been shown to represent the current gold standard in ovarian cancer as a prerequisite to PARPi challenge [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular scale, a germline mutation in BRCA1 or BRCA2 ( gBRCA1/2 ) is found in 15–20% of patients with TNBC [ 5 , 6 ]. The disruption of BRCA1/2 genes leads to inefficient homologous recombination (HR) for double-strand break (DSB) processing, leading to the so-called homologous recombination deficiency (HRD) and subsequent specific features through genomic instability [ 7 ]. In the context of neoadjuvant chemotherapy, it has been shown that tumors with BRCA1/2 mutations exhibit an increased sensitivity to platinum salts [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from germline mutations, somatic mutations in BRCA1 or BRCA2 are found in an additional 4% and 3% of cases, respectively [ 7 ]. BRCA -mutated tumors have been reported to exhibit specific features, such as enhanced sensitivity to antineoplastic agents [ 8 ]. Nevertheless, BRCA1 and BRCA2 may have distinct impact on prognosis; several studies suggested that BRCA2 mutations are associated with a better prognosis than BRCA1 -mutated and non-mutated patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%